Chaotic Image Encryption with Random Shuffling of Data - Murat Aydos; Alper Uğur (Pamukkale University Journal of Engineering Sciences, 2014)
Security of valuable multimedia contents such as images in personal photograph albums, electronic publishing, frames of multicast video conference can be achieved by image encryption. Secure transmission of these contents is required to be rapid, efficient and practical. Hence, image encryption process must be chosen not only to satisfy the security goals but also to fulfill these requirements. Due to the inadequacy and inefficiency of conventional text based information encryption methods, researchers have proposed several encryption schemes. Many of them are based on chaotic algorithms. Recently, the studies are concentrated on some weaknesses of chaotic algorithms and most of the presented solutions came up with complex structured chaotic maps. In this paper, we present a self-diagonal shuffler mechanism embedded to one dimensional chaotic encryption system to overcome its leak points while keeping simplicity and efficiency properties.